The performance of earth retention pond water retain capability using geotechnical properties evaluation - Zainal Abidin, Mohd Hazreek; Adnan, Mohd Shalahudin; Madun, Aziman; Abu Talib, Mohd Khaidir; Kamarudin, Ahmad Fahmy; Mohamad Ismail, Mohd Ashraf; Ishak, Mohd Fakhrurrazi (Science Publishing Corporation, 2018)
Development of a new modern housing areas has demand a retention pond for recreation activity and landscaping purposes. This study deals with the evaluation of water retain ability of a new retention pond from the soil condition perspective. Geotechnical laboratory testing was performed via particle size distribution, Atterberg limits and permeability to assess the retention pond soil condition. All the experiment was performed according to British Standard 1377 (1990). It was found that soil tested has been dominated by fine particles which ranged at 30.84 – 60.88 % compared to the coarse particles (sand and gravel). Atterberg limits results has found that all soil tested has a liquid limit (LL), plastic limit (PL) and plasticity index (PI) that was varied at 29 – 74 %, 16.9 – 33.6 % and 17 – 40.4 % respectively representing its promising water retain capability. Moreover, permeability result founds that all values of permeability coefficient, k was ranged at 3.11 x 10-4 – 5.65 x 10-7 cm/s thus conclude that all soil tested has low to very low degree of permeability. Finally, retention pond of a new development area has been evaluated directly according to its soil condition thus provide some valuable information to the responsible parties regarding the future planning and decision making of the sustainable catchment areas.